Pengaruh Pemberian Limbah Kulit Kopi (Coffea sp.) Amoniasi Sebagai Pakan Alternatif Terhadap Pertambahan Bobot Ayam Broiler - Muhammad Khalil (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2016)
The objective of this study was to determined the effect of giving coffee waste ammoniation as alternative feed to body weight of broilers. This study used experimental method with quantitative approach. The study was designed with Completely Randomized Design (CRD) consists of 6 giving treatments contained different concentration of coffee waste ammoniation, consists of P0: Positive Control, P1: 0%, P2: 5%, P3: 10%, P4: 15% and P5: 20% with 4 repetition in each treatment. Factor measured as a parameter in the study was body weight of broilers for 6 weeks as measured by 2nd week, 4th and 6th. The data were analyzed using analysis of variance (ANOVA) α0.05 as well as a further test by Least Significant Difference (LSD) and Honestly Significant Difference (HSD). The results showed that giving coffee waste ammoniation was effected on body weight of broilers. Optimal body weight of broiler in 2nd week was obtained in giving treatment with concentration of 15% coffee waste ammoniation, which average body weight of 512.5 g, for the 4th week of treatment with concentration of 10% which average body weight of 1092.5 g, and for the 6th week of the treatment with a concentration of 15% which average body weight of 1535 g. It was concluded that giving coffee waste ammoniation as much as 15% over 42 days can increase bodu weight of broilers.